Penguatan Proses Pengajaran Thaharah Cara Berwudhu di MADIN Miftahul Ulum Kesugihan - Febri Sapitri; Diyan Putri Ayu (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research is in the background of how important the teaching of ablution is in Madrasah Diniyah Miftahul Ulum Kesugihan Pulung Ponorogo, where the environment still holds the jawen Islam. The child already knows the ablution, but if the child is asked to practice the steps of the wudhu, the child often does not sequence according to the steps of the ablution and even sometimes the child forgets one of the steps. The selection of the